Pulling, encountering or through proxies? Everyday life information seeking and the use of the Internet in China - Yan, P (2019)
Chinese Internet users have in recent years experienced increasingly diversified choices of information formats (text, short videos, and stream videos), information content (news, fictions, and lifestyle), as well as information platforms(news apps, search engines, and mobile social media). Chinese booming digital cultural industry has created a dynamic information ecology for grassroots Internet users. Meanwhile, Chinese Internet users have employed different approaches to collecting, distinguishing, and handling information available online, with some more sophisticated than the others in managing the massive amount of information and identify misinformation or disinformation. While previous empirical research on Chinese Internet has focused on the how the Internet has influenced economic activities, political participation, and social networks, yet little is known about how Chinese Internet users seek information on the Internet: What information sources do they trust? What information categories are considered essential for different user groups? What are the main concerns users have during the information-seeking process? Whether or not differentiated information-seeking practices could result in a new form of the digital divide? Answering these questions will help to build a deeper understanding of how Chinese users domesticate the Internet into users’ daily lives as not only a tool of communication but also a gateway to informationseeking. In this paper, I will combine survey data collected from two randomly selected samples in a village (N1 = 128) and a factory (N2 = 229), 55 individual interviews, and four focus group studies, to study information-seeking practices in digital era among rural and urban Internet users in Central China. The paper will start with a quantitative analysis of information sources, information categories, and 3 information-seeking process and their relationship with demographic and Internet use variables. To understand different contexts in information-seeking practices, I will use qualitative data to focus on three approaches to information seeking, namely, pulling from search engines, information seeking through encountering, and information seeking through information proxies. I aim to explore how the Internet has embedded into individuals’ everyday lives as an information channel, what different information-seeking approaches and strategies employed. Findings from this research will enrich the understanding of the complexities and nuances of using the Internet for everyday information-seeking practices in China and will also reveal how Chinese grassroots users perceive the Internet in a marketplace of digital information.